Reading and linguistic awareness - Flôres, Onici Claro (2018)
This article considers reading as a complex cognitive activity that necessarily involves the development of linguistic awareness of the beginners, starting with the phonological one. In its viewpoint, learning reading demands the establishment of connections between speech and the written system, since the Brazilian written system is alphabetic. Concerning the teaching of reading, it proposes that teachers should take into account the biological foundations of language and the phonological principles of Brazilian Portuguese. In addition, it stresses the importance of contextualizing the process of teaching reading to the learners’ social and culturalcontext, without ignoring their prior knowledge.